Hermeneutiek in veelvoud - Bernaerts, Lars (Cahier voor Literatuurwetenschap, 2011)
What will be the future role of hermeneutics in literary theory? Can we shape the future of hermeneutics by going back to its tradition and by looking at the way hermeneutics is relevant in other disciplines? The new issue of Cahier voor Literatuurwetenschap has two objectives. First, we wish to study the role of hermeneutics in other disciplines, such as the philosophy of history, theology, and the cognitive sciences. It will be clear that literary theory benefits from this interdisciplinary exercise. Second, we will have a closer look at the hermeneutical tradition in literary theory. Important chapters from the history of hermeneutics (e.g., Schleiermacher, Heidegger, Iser) are revisited and its influence in recent theoretical developments is considered.